Prevalence of maxillofacial injuries in women who have experienced physical violence reported at a house of justice in the metropolitan area of Bucaramanga (Colombia) - Contreras-Ochoa, Ingrid Johanna; Portillo-Vilardy, Edna Mariam; Rodríguez, Martha Juliana (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: the data on physical violence against women in Colombia are high, with the face being one of the most affected regions; however, data on injuries types is limited. The aim of this study was to determine the prevalence of maxillofacial lesions caused by physical violence in women who have reported such violence at a House of Justice in the metropolitan area of Bucaramanga (Colombia) from September 2013 to March 2015. Methods: a descriptive prevalence study was conducted in 258 expert reports filed on the aforementioned dates. Sociodemographic variables, lesion types and aggressor characteristics were analyzed; data was collected through an instrument created based on the parameters of the National Institute for Legal Medicine and Forensic Sciences. Frequencies and proportions were calculated for qualitative variables, as well as measures of central tendency and dispersion for quantitative variables. The Chi2 test or Fisher’s Exact test were used for bivariate analysis as needed. A p value lower than 0.05 was considered statistically significant. Results: the women/men ratio was 2.8. The prevalence of maxillofacial injuries was 55.4% when considering 157 expert reports of women 18 years of age or older. In 81 reports (93.1%) the aggressor was known and in 47 cases (58%) the aggressor was the husband. Conclusions: the prevalence of maxillofacial injuries was 55.4%, with hematoma being the most common type of injuries as related in 49 reports (56.3%).